Pengaruh PAD dan DAU terhadap Belanja Modal di Kabupaten Hulu Sungai Selatan - Ilmi, Zainal; Saleh, Muhammad (PPJP ULM, 2019)
The purpose in this research is to know effect partially and simultaneously of PAD andDAU to BM in Hulu Sungai Selatan regency. The data research from DJPK Kemenkeu RIwhich the data research is LRA APBD of Hulu Sungai Selatan regency 2003-2017 and typedata of research is time series data, then technical analysis used multiple linear regressionanalysis. The result of research showed PAD has negative and not significant effect to BM inHulu Sungai Selatan Regency 2003-2017, DAU has positive and significant effect to BM inHulu Sungai Selatan Regency 2003-2017, then by simultaneously or together, PAD and DAUhave significant effect to capital expenditure in Hulu Sungai Selatan Regency 2003-2017.